Predictors of Senior Center Use among Older Adults in New York City Public Housing - Schneider, Amanda E. (J Urban Health, 2014)
Despite agreement among stakeholders that senior centers can promote physical and mental health, research on senior center use in urban populations is limited. Our objective was to describe demographic and health factors associated with senior center use among urban, low-income older adults in order to inform programming and outreach efforts. We used data from a 2009 telephone survey of 1036 adults randomly selected from rosters of New York City public housing residents aged 65 and older. We analyzed senior center use by race/ethnicity, age, gender, health, housing type, and income, and used a forward selection approach to build best-fit models predicting senior center use. Older adults of all ages and of both genders reported substantial use of senior centers, with nearly one third (31.3%) reporting use. Older adults living alone, at risk of depression, or living in specialized senior housing had the greatest use of centers. Senior center use varied by race/ethnicity, and English-speaking Hispanics had a higher prevalence of use than Spanish-speaking Hispanics (adjusted prevalence ratio [PR]=1.69, 95% CI: 1.11-2.59). Spanish-speaking communities and older adults living in non-senior congregate housing are appropriate targets for increased senior center outreach efforts.